Introduction to coordination chemistry - Lawrance, Geoffrey A (Chichester, U.K. : Wiley, 2010)
"Written in a highly readable, descriptive and accessible style, Introduction to Coordination Chemistry describes properties of coordination compounds such as colour, magnetism and reactivity as well as the logic in their assembly and nomenclature. It is illustrated with many examples of the importance of coordination chemistry in real life, and includes extensive references and a bibliography." "Introduction to Coordination Chemistry is a comprehensive and insightful discussion of one of the primary fields of study in Inorganic Chemistry for both undergraduate and non-specialist readers."--BOOK JACKET
-- The central atom -- Key concepts in coordination chemistry -- A who's who of metal ions -- Metals in molecules -- The road ahead -- Ligands -- Membership: being a ligand -- Monodentate ligands - the simple type -- Greed is good - polydentate ligands -- Polynucleating species - molecular bigamists -- A separate race - organometallic species -- Complexes -- The central metal ion -- Metal-ligand marriage -- Holding on - the nature of bonding in metal complexes -- Coupling - polymetallic complexes -- Making choices -- Complexation consequences -- Shape -- Getting in shape -- Forms of complex life - coordination number and shape -- Influencing shape -- Isomerism - real 3D effects -- Sophisticated shapes -- Defining shape -- Stability -- The makings of a stable relationship -- Complexation - will it last? -- Reactions -- Synthesis -- Molecular creation - ways to make complexes -- Core metal chemistry - Periodic table influences -- Reactions involving the coordination shell -- Reactions involving the metal oxidation state -- Reactions involving coordinated ligands -- Organometallic synthesis -- Properties -- Finding ways to make complexes talk - investigative methods -- Getting physical - methods and outcomes -- Probing the life of complexes - using physical methods -- A complex life -- Life's a metal ion -- Metalloproteins and metalloenzymes -- Doing what comes unnaturally -- A laboratory-free approach - in silico prediction -- Complexes and commerce -- Kill or cure? - Complexes as drugs -- How much? - Analysing with complexes -- Profiting from complexation -- Being green -- Complex futures -- Appendix A: nomenclature -- Appendix B: molecular symmetry: the point group
Includes bibliographical references and index
Keywords: Coordination compounds; Coordination compounds -- Magnetic properties; Chemistry, Inorganic